The Emerging Role of Long Non-Coding RNAs in Esophageal Cancer: Functions in Tumorigenesis and Clinical Implications - Han, Yali; Zhao, Guo; Shi, Xinhang; Wang, Yushan; Wen, Xin; Zhang, Lu; Guo, Xiangqian (Frontiers in Pharmacology, 2022)
Esophageal cancer (EC) is one of the most common malignancies of digestive tracts with poor 5 years survival rate. Hence, it is very significant to further investigate the occurrence and development mechanism of esophageal cancer, find more effective biomarkers and promote early diagnosis and effective treatment. Long non-coding RNAs (lncRNAs) are generally defined as non-protein-coding RNAs with more than 200 nucleotides in length. Existing researches have shown that lncRNAs could act as sponges, guides, scaffolds, and signal molecules to influence the oncogene or tumor suppressor expressions at transcriptional, post-transcriptional, and protein levels in crucial cellular processes. Currently, the dysregulated lncRNAs are reported to involve in the pathogenesis and progression of EC. Importantly, targeting EC-related lncRNAs through genome editing, RNA interference and molecule drugs may be one of the most potential therapeutic methods for the future EC treatment. In this review, we summarized the biological functions and molecular mechanisms of lncRNAs, including oncogenic lncRNAs and tumor suppressor lncRNAs in EC. In addition, we generalized the excellent potential lncRNA candidates for diagnosis, prognosis and therapy in EC. Finally, we discussed the current challenges and opportunities of lncRNAs for EC.